Relationship between teacher nonverbal behaviors in the classroom and students' learning - Manalansan, Grettel M.; Caparas, Maria Veronica G. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2002)
This thesis examines the relationship of teacher nonverbal communication, specifically non-verbal immediacy behaviors, affective learning, and student perceived cognitive learning. The researcher had the following objectives in mind: 1. to find out if there is a relationship between teacher nonverbal immediacy and affective learning; 2. to find out if a relationship exists between affective learning and cognitive learning; 3. to determine if the relationship of teacher nonverbal immediacy, affective learning, and cognitive learning is linear; and 4. to note the effects, if any, of intervening variables such as teacher gender, class size, and teacher talk time on students' affective learning and cognitive learning.
Thesis (Bachelor of Arts in Speech Communication)
Keywords: Nonverbal communication in education; Cognitive learning; Affective education